2016
DOI: 10.1098/rspb.2016.0692
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic modulation of visual contrast discrimination triggered by action

Abstract: Recent evidence suggests that ongoing brain oscillations may be instrumental in binding and integrating multisensory signals. In this experiment, we investigated the temporal dynamics of visual-motor integration processes. We show that action modulates sensitivity to visual contrast discrimination in a rhythmic fashion at frequencies of about 5 Hz (in the theta range), for up to 1 s after execution of action. To understand the origin of the oscillations, we measured oscillations in contrast sensitivity at diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
94
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(104 citation statements)
references
References 56 publications
(78 reference statements)
9
94
1
Order By: Relevance
“…Both suppression and enhancement are independent of stimulus eccentricity (Knöll et al, 2011) and thus are unlikely generated by spatial attention, which shifts from fixation to saccadic target very early, ϳ300 ms before saccadic onset (Kowler et al, 1995;Deubel and Schneider, 1996;Rolfs and Carrasco, 2012). The perisaccadic suppression and the subsequent enhancement form a cycle of an oscillation at ϳ3 Hz, suggesting that they might be part of a more prolonged oscillation linked to saccadic preparation, similarly to the visual oscillation demonstrated in preparation of an hand action (Tomassini et al, 2015;Benedetto et al, 2016).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Both suppression and enhancement are independent of stimulus eccentricity (Knöll et al, 2011) and thus are unlikely generated by spatial attention, which shifts from fixation to saccadic target very early, ϳ300 ms before saccadic onset (Kowler et al, 1995;Deubel and Schneider, 1996;Rolfs and Carrasco, 2012). The perisaccadic suppression and the subsequent enhancement form a cycle of an oscillation at ϳ3 Hz, suggesting that they might be part of a more prolonged oscillation linked to saccadic preparation, similarly to the visual oscillation demonstrated in preparation of an hand action (Tomassini et al, 2015;Benedetto et al, 2016).…”
Section: Introductionmentioning
confidence: 80%
“…Brain oscillations might be important in binding and integrating sensorimotor information (Engel et al, 2001) via a shared internal oscillator that coordinates the two systems. Recent experiments have shown that voluntary movements can synchronize oscillations of visual performance (Tomassini et al, 2015;Benedetto et al, 2016). Therefore, action not only interferes with perception through a single transient suppression at around movement time (a phenomenon called "motorinduced suppression"), but rhythmically interacting long before and after action execution.…”
Section: Introductionmentioning
confidence: 99%
“…There is a growing body of evidence for a rhythmic component of human perception and behaviour supported by neural oscillations (Benedetto et al, 2016;Fiebelkorn et al, 2013;Landau and Fries, 2012;VanRullen et al, 2011;Zoefel and VanRullen, 2017). Correspondingly, there is an increased interest in investigating how certain measures of performance (from the detection of simple stimuli such as pure tones, to more complex tasks such as speech comprehension) vary with the phase of ongoing neural oscillations (e.g., Baumgarten et al, 2015;Busch et al, 2009;Henry et al, 2014;Henry and Obleser, 2012;Ng et al, 2012;Riecke et al, , 2015aRiecke et al, , 2015bStrauß et al, 2015;Zoefel et al, 2018;Zoefel and Heil, 2013;Zoefel and VanRullen, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies investigating cardiac influences on perception and cognition have only employed passive stimulus presentation, which ignores self-initiated action as a crucial dimension of sensory and particularly visual processing. Mediating our engagement with a visual scene, motor actions dynamically orchestrate incoming sensory data and thus strongly influence visual perception-selecting what information is preferentially processed (Benedetto, Spinelli, & Morrone, 2016;Tomassini, Spinelli, Jacono, Sandini, & Morrone, 2015). Sensorimotor coupling has also been linked to periodic attentional fluctuations (Hogendoorn, 2016;Morillon, Schroeder, & Wyart, 2014).…”
Section: Introductionmentioning
confidence: 99%